Application of a model-based design tool X2C in induction machine vector control - Lopac, Nikola (Array, 2019)
Open source software tools for model-based design of embedded control systems represent a new method for rapid development and testing of advanced control structures in modern electric drives. The new concept of one of those tools, X2C, is presented in this paper, and in order to evaluate its performance in the development of complex control systems, it is applied to implement induction machine vector control. Based on the simulation model of the drive developed in PLECS, the parameters of the controllers were determined. The algorithm for the vector control of the induction machine was developed in X2C, implemented on the digital signal processor and applied to the real system. The system was tested during the no-load acceleration, deceleration, and reversing of the motor, while measuring the electrical and mechanical variables. Finally, the quantitative comparison of the experimental results and the results obtained by the equivalent simulations, based on the Integral Squared Error criterion, revealed that these results were well matched. This finding suggested that the control system was successfully implemented, thereby confirming the effectiveness of X2C tool in this particular type of application. With this work it has been shown that a transition from simulation to actual environment is rapidly achieved, with a simple verification of implemented methods accompanying the process. Realization of this work is a step forward in the utilization of open source software packages for implementation of induction machine vector control with the purpose of rapid verification of simulation models.